A Comprehensive Evaluation of Xpert MTB/RIF Assay With Bronchoalveolar Lavage Fluid as a Single Test or Combined With Conventional Assays for Diagnosis of Pulmonary Tuberculosis in China: A Two-Center Prospective Study - Pan, Xiaofu; Yang, Shoufeng; Deighton, Margaret A.; Qu, Yue; Hong, Liang; Su, Feifei (Frontiers in Microbiology, 2018)
Abstract Introduction: The Xpert MTB/RIF is recommended by the World Health Organisation as a first line rapid test for the diagnosis of pulmonary tuberculosis (TB); however, China does not routinely use this test, partially due to the lack of a sufficient number of systematic evaluations of this assay in local patients. The aims of this study were to comprehensively assess the diagnostic performance of Xpert MTB/RIF, either alone or in combination with conventional assays for the diagnosis of pulmonary TB in adult Chinese patients. Methods: Xpert MTB/RIF tests were performed in 190 adult patients with suspected pulmonary TB, using bronchoalveolar lavage fluid (BALF) as test specimens. In parallel, conventional tests were carried out using the same BALF samples. Using two different reference standards, the performance of Xpert MTB/RIF, conventional assays, and their combinations were evaluated. Results: Using mycobacterial culture as the reference comparator, Xpert MTB/RIF was found to be superior to smear-microscopy in detecting Mycobacterium tuberculosis. When final diagnosis, based on clinical criteria, was employed as the reference standard, Xpert MTB/RIF showed an even higher accuracy of 72.1%, supported by a sensitivity of 61.1% and specificity of 96.6%. Xpert MTB/RIF also demonstrated a powerful capability to identify pulmonary TB cases undetected by culture or smear-microscopy. Combining smear-microscopy and Xpert MTB/RIF was found to be the most accurate early predictor for pulmonary TB. Rifampicin resistance reported by Xpert MTB/RIF slightly deviated from that by phenotypic antibiotic susceptibility testing and requires further study with a larger sample size. Conclusion: This two-center prospective study highlights the value of Xpert MTB/RIF with BALF in diagnosing pulmonary TB in adult Chinese patients. These findings might contribute to the optimization of current diagnostic algorithms for pulmonary TB in China.